2002
DOI: 10.1002/dc.10009
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilariasis of breast: Report of two cases diagnosed by fine‐needle aspiration biopsy

Abstract: We report on 2 cases of dirofilariasis of the breast occurring in adult Chinese females residing in Hong Kong. The diagnosis was made by fine-needle aspiration biopsies. The direct smears contained numerous acute inflammatory cells, including eosinophils. A partially necrotic adult nematode of about 400-450 microm in diameter was identified in the cell-block sections of each case. The worm was characterized by a thick cuticle with longitudinal cuticular ridges and fine transverse surface striations, abundant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In Hong Kong, two cases of breast lesion due to D. repens based on morphological features have been reported (17). On the other hand, D. immitis is usually associated with pulmonary nodules (16).…”
Section: Discussionmentioning
confidence: 99%
“…In Hong Kong, two cases of breast lesion due to D. repens based on morphological features have been reported (17). On the other hand, D. immitis is usually associated with pulmonary nodules (16).…”
Section: Discussionmentioning
confidence: 99%
“…Also none of the previous cytologic reports of dirofilariasis detected microfilariae or eggs on aspirated smears. [5][6][7] The present case was unique because of detecting microfilariae in material aspirated from a subcutaneous mass and later detecting gravid adult female Dirofilaria worms in histologic sections. The presence of many microfilariae in aspirated material indicated that the needle was inserted into the gravid uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients presented with breast masses, and others had retroperitoneal, facial and lung masses. [5][6][7] In none of them was dirofilariasis suspected before FNA. Also none of the previous cytologic reports of dirofilariasis detected microfilariae or eggs on aspirated smears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcutaneous migration of the worm may result in local swellings with changing localisation (creeping eruption) [31]. In addition, rare cases of organ manifestation have been reported, affecting the scrotum, male genitals, female breast, lymphatic glands and peritoneum [2,[32][33][34][35][36][37][38]. OD is a variation of subcutaneous dirofilariasis with parasite localisation in the eye area [30].…”
Section: Introductionmentioning
confidence: 99%